Human Resource Management in New Public Management Paradigm - Jandeang, Burachat; Yupas, Assoc. Prof. Dr. Yupaporn (Journal for Developing the Social and Community, 2017)
The change of Human Resource Management emerged at present has been significantly influenced by New Public Management (NPM). Based on this concept, government agencies are required to make improvement in many aspects including their roles, organizational model, management system, budget system, human The change of Human Resource Management emerged at present has been significantly influenced by New Public Management (NPM). Based on this concept, government agencies are required to make improvement in many aspects including their roles, organizational model, management system, budget system, human